Conducting Nuclear Security Culture Self-Assessments in Nuclear Research Facilities Using the IAEA Methodology - Anhar Riza Antariksawan; Khairul Khairul; Heru Umbara; Endang Kristuti; Bayu Purnomo (International Journal of Nuclear Security, 2018)
The National Nuclear Energy Agency of Indonesia (BATAN) has promoted the culture and assessment of nuclear security in Indonesia since 2010. After conducting a successful trial assessment in 2012, BATAN performed a second self-assessment in 2015 in three nuclear facilities. The assessment's methodology followed the guidelines set by the International Atomic Energy Agency (IAEA). The objective of this paper is to demonstrate the techniques used in applying the IAEA methodology and to discuss the primary outcomes of the assessment. The data collection consisted of surveys, interviews, document reviews, and observations. A total of about 50% of the three facilities’ employees participated in the survey and/or interview process. Three categories of sub-cultures—security personnel, non‑structural personnel, and structural personnel—were assessed, covering a range of twelve general characteristics and thirty indicators of security culture. An overall average score of 5.25 on a 7-point scale was obtained from the survey. A consolidated assessment of the results from all data collection techniques showed that most of the security culture characteristics assessed reflected some of the anticipated best practices and also demonstrated strengths necessary in security culture. However, certain aspects of leadership behavior need to be enhanced, especially ones relating to motivation. By examining the results from the three different subcultures, it became clear, especially to the researchers and administrative personnel, that further dissemination of nuclear security concepts and policy is needed. The methodology for the IAEA’s nuclear security culture self-assessment has been successfully implemented and has resulted in positive outcomes. The potential improvement of assessment implementation should also be considered, such as in the development of survey questions and the selection of indicators to be elaborated on interviews.
Keywords: security culture; self-assessment; IAEA methodology